ANALYZING ATTITUDES TOWARDS SCIENCE AND RELIGION BETWEEN NATIONAL AND ISLAMIC SCHOOLS IN INDONESIA: A CASE STUDY - Saputra, Winata Tegar; Winarno, Nanang; Rusyati, Lilit; Firdaus, Rohim Aminullah; Mustikasari, Vita Ria (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
Given that Muslims make up the majority in Indonesia, students' perspectives on science are influenced by their religious beliefs. This research aims to analyze the differences in attitudes toward science and religion between national and Islamic schools. This study employed a survey method to look at the views of students in national and Islamic schools. Two groups comprise the 420 Indonesian secondary school students that comprise the research sample: 212 students from national schools and 208 from the renowned "Pesantren" Islamic school in Kota Bandung, West Jawa. The result of this study shows factors with significant differences in general aspects between national school with 3.5 and islamic school with 3.8. The aspect that show significant differences are competitiveness, critical thinking, religiosity, trust in scientists, interest in doing science, extrinsic motivation for science, general value of science, awareness of environmental issues, science self-concept, science removing the need for God, compatibility between science and religion, and perceptions of science lessons. Factors with no significant differences include attitudes toward theistic faith, creationism, the public value of science, and scientism. Additionally, there are some strengths and weaknesses between the national school and Islamic school, such as the time of the science lessons, lab equipment, internet access, etc. It could be concluded that national school and islamic school has strengths and weaknesses that related with science and religion.